الهدي النبوي في تأهيل الجناة - الشريفين، محمد عيسى إبراهيم (جامعة الملك فيصل, 2017)
لقد نالت شريحة الجناة حظا وافرا من العناية النبوية، وقدمت الأحاديث النبوية حزمة من الوسائل التي تهدف إلى إعادة إصلاح وتأهيل الجناة، كما قدمت الرعاية النفسية والمادية لهم، وقد اتضح ذلك من خلال إجراءات البحث التي تناولت أساليب التأهيل النفسي والمادي للجناة. فعلى المستوى النفسي: نفرت الأحاديث النبوية من الجناية، وأكدت مفهوم التوبة الذي هو مفتاح عملية التأهيل، وقدمت للجاني حق الالتجاء لله بالدعاء، وبينت له أن باب التوبة لا يوصد. أما على المستوى المادي: فقد طالبت السنة النبوية المجتمع بالوقوف إلى جانب الجاني ماديا، ومساعدته لكي يتخطى محنته، وطالبت السنة بتعليم الجاني وتثقيفه، وغير ذلك من الخطوات التي من شأنها إعادة إصلاحه وتأهليه. وتوصل البحث إلى مجموعة من النتائج منها أن السنة النبوية قدمت الطريقة المثلى في التعامل مع الجناة، وأن السنة لم تكتف بإيصال المجرم إلى حالة التوبة، بل حرصت على إدماجه في المجتمع لكي يصبح عضوا صالحا ينتفع به. كما أشارت النتائج إلى وجود منظومة متكاملة في السنة النبوية للتعامل مع الجناة بهدف تأهيلهم.
Offenders were granted good share of the prophet (PBUH) care. Prophet's traditions presented a group of methods that aimed to rehabilitate offenders. It also provided psychiatrics and financial support for them. This was clearly revealed in this work. On psychiatrics level, the prophet's traditions alienated misconducts and emphasized that repentance is the key for rehabilitation. It also provided the right to refuge to god by supplication and indicated that repentance path will not be obstructed. On financial level, prophet traditions asked the society to financially support and assist offenders to overcome his ordeal. It also asked for educating offenders in a group of commands that aimed to rehabilitate and qualify offenders. The work also indicated that prophet tradition provided an ideal method to deal with offenders. It did not settle on driving offender to repentance only, but was keen to incorporate him in the society as a good useful citizen. The results also indicated the presence of an integrated system of prophet traditions for rehabilitation.
Keywords: الأحاديث النبوية -- تأهيل الجناة -- إصلاح الجناة -- التأهيل النفسي -- التأهيل المادي